The effect of pastoral assistance programs on mental health and resilience of congregational members who lost their jobs during the Covid-19 pandemic - Hutabarat, Bernard Maruli; Hutagalung, Stimpson; Hendriks, Alvyn Cesarianto; Ferinia, Rolyana (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study aimed to determine the effect of the pastoral care program on the mental health and resilience of church members who lost their jobs during the COVID-19 pandemic. The research method used is quantitative using the Correlated T-test data analysis technique. The research found that the pastoral assistance program applied to congregations who lost their jobs during the COVID-19 pandemic had a significant positive effect on mental health. Likewise, the results of the analysis of the pastoral assistance program applied to congregations who lost their jobs during the COVID-19 pandemic on the resilience of church congregations. So it can be said that there is a significant effect of the pastoral assistance program on the mental health and resilience of the congregation who lost their jobs during the COVID-19 pandemic. Pastoral assistance programs are essential to provide, considering their various functions that impact mental health and provide a complete self-understanding for the community. The congregation is to be able to have resilient behavior where this is important to adapt and lead a normal lifestyle despite losing a job during the COVID-19 pandemic.